To determine which equation has a solution of \( x = -12 \), we can substitute \( x \) with \(-12\) in each equation and see if the equation holds true.
-
Equation: \( x + 12 = -1 \) \[ -12 + 12 = 0 \quad (\text{not true}) \]
-
Equation: \( x + \frac{1}{2} = -1 \) \[ -12 + \frac{1}{2} = -11.5 \quad (\text{not true}) \]
-
Equation: \( x - 1 = -12 \) \[ -12 - 1 = -13 \quad (\text{not true}) \]
-
Equation: \( x - \frac{1}{2} = -12 \) \[ -12 - \frac{1}{2} = -12.5 \quad (\text{not true}) \]
-
Equation: \( x + 1 = 12 \) \[ -12 + 1 = -11 \quad (\text{not true}) \]
-
Equation: \( x - 12 = 1 \) \[ -12 - 12 = -24 \quad (\text{not true}) \]
Upon evaluating all equations, none yield a true statement when substituting \( x = -12\).
Therefore, the answer is none of the given equations have a solution of \( -12 \).